Induction Chemotherapy in Technically Unresectable Locally Advanced Carcinoma of Maxillary Sinus. (11th May 2014) - Noronha, Vanita; Patil, Vijay Maruti; Joshi, Amit; Krishna, Muddu Vamshi; Dhumal, Sachin; Juvekar, Shashikant; Pai, P.; Chatturvedi, Pankaj; Chaukar, Devendra Arvind; Agarwal, Jai Prakash; Ghosh, Sarbani; Murthy, Vedang; et al.
Abstract : Background . Locally advanced carcinoma of maxillary sinus has been historically reported to have poor prognosis. We evaluated the role of NACT in improving the outcome in these patients. Methods . 41 patients with locally advanced technically unresectable (stage IVa) or unresectable maxillary carcinoma (stage IVb) were treated with induction chemotherapy between 2008 and 2011. The demographic profile, response and toxicity of chemotherapy, definitive treatment received, progression free survival (PFS), and overall survival (OS) were analyzed. Univariate and multivariate analysis were performed to determine factors associated with PFS and OS. Results . The chemotherapy included two drugs (platinum and taxane) in 34 patients (82.9%) and three drugs (platinum, taxane, and 5 FU) in 7 (17.1%). There was no complete response seen in any of the patients, stable disease in 18 (43.9%), partial response in 16 (39%), and progression in 7 (17.1%) patients. After induction, the treatment planned included surgery in 12 (29.3%), CT-RT in 24 (58.5%), radical RT in 1 (2.4%), palliative RT in 1 (2.4%), and palliative chemotherapy in 3 (7.3%) patients. Overall, the median PFS was 10.0 months. The OS at 24 months and 36 months was 41% and 35%, respectively. Conclusion . In unresectable maxillary carcinoma, induction chemotherapy has clinically significant benefit with acceptable toxicity.